Taxonomic notes on Goodyera (Goodyerinae, Cranichideae, Orchidoideae, Orchidaceae) in China and an addition to orchid flora of Vietnam - Liu, Yan Wen; Zhou, Xiao Xu; Schuiteman, André; Kumar, Pankaj; Hermans, Johan; Chung, Shih Wen; Tian, Huai Zhen (Phytotaxa, 2019)
Based on fieldwork and examination of fresh as well as preserved specimens, Goodyera bomiensis and G. wolongensis are reduced under the synonymy of G. brachystegia and G. serpens respectively. Goodyera serpens and G. marginata are re-instated as accepted species, and G. afzelii, previously thought to be restricted to Madagascar and Mozambique, is added to the orchid flora of Vietnam.